Rats Synchronize Locomotion with Ultrasonic Vocalizations at the Subsecond Time Scale - Laplagne, Diego A.; Elías Costa, Martín (Frontiers in Behavioral Neuroscience, 2016)
Acoustic signals have the potential for transmitting information fast across distances. Rats emit ultrasonic vocalizations of two distinct classes: ‘22-kHz’ or ‘alarm’ calls and ‘50-kHz’ calls. The latter comprises brief sounds in the 30–80 kHz range, whose ethological role is not fully understood. We recorded ultrasonic vocalizations from pairs of rats freely behaving in neighboring but separated arenas. 50-kHz vocalizations in this condition were tightly linked to the locomotion of the emitter at the subsecond time scale, their rate sharply increasing and decreasing prior to the onset and offset of movement respectively. This locomotion-linked vocalization behavior showed a clear ‘audience effect’, as rats recorded alone displayed lower vocal production than rats in social settings for equivalent speeds of locomotion. Furthermore, calls from different categories across the 50-kHz and 22-kHz families displayed markedly different correlations with locomotor activity. Our results show that rat vocalizations in the high ultrasonic range are social signals carrying spatial information about the emitter and highlight the possibility that they may play a role in the social coordination of spatial behaviors.